2021
DOI: 10.1093/pm/pnab229
|View full text |Cite
|
Sign up to set email alerts
|

Pain Location Is Associated with Fracture Type in Acute Osteoporotic Thoracolumbar Vertebral Fracture: A Prospective Observational Study

Abstract: Objective This study investigated the relationship between pain location and fracture type in the patients with acute osteoporotic vertebral fracture (OVF). Design A prospective observation study. Subject A total of 306 patients with acute OVF were included. Methods The site of pain of each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Secondly, we also found that OVCF patients with kyphosis had higher postoperative VAS scores and less pain relief. We speculate that this may be related to the severity of vertebral fracture ( 20 ), namely, burst fracture (or vertebral posterior margin fracture) and combined kyphosis suggested severe injury violence and vertebral fracture. In addition, we found that patients with thoracolumbar vertebral fracture had more obvious pain relief after PKP, while patients with thoracic or lumbar vertebral fracture had higher postoperative VAS scores, which may be related to higher anatomical stability of thoracic vertebral segments ( 21 ).…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, we also found that OVCF patients with kyphosis had higher postoperative VAS scores and less pain relief. We speculate that this may be related to the severity of vertebral fracture ( 20 ), namely, burst fracture (or vertebral posterior margin fracture) and combined kyphosis suggested severe injury violence and vertebral fracture. In addition, we found that patients with thoracolumbar vertebral fracture had more obvious pain relief after PKP, while patients with thoracic or lumbar vertebral fracture had higher postoperative VAS scores, which may be related to higher anatomical stability of thoracic vertebral segments ( 21 ).…”
Section: Discussionmentioning
confidence: 97%
“…OP is considered a silent disease, but pain is still one of the first complaints of those patients. Usually, OP patients experience two types of pain: acute pain, usually related to fractures (Zhang et al., 2021) (when, usually, the disease is diagnosed) and chronic pain, usually low back pain. In this case, pain includes peripheral characteristics–such as postural alterations, fractures and associated muscle atrophy (Catalano et al., 2017) – but also has influence of the psychosocial context, which can make the pain experience even worse (Raja et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that people with osteoporosis and osteopenia exhibit a functional decline in balance (Aveiro et al., 2017) and mobility (Murtezani et al., 2014), which are both variables that increase the risk of falling (Zhang et al., 2021). Therefore, it is crucial that the treatment protocol aims to improve these functions in order to prevent falling and the resulting fractures (Trevisan et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Thoracolumbar osteoporotic vertebral fractures (TLOVFs) are the most common complication of osteoporosis and can not only affect patients' work and daily life but also lead to other functional disorders, spinal deformities, and sometimes even paralysis. [5][6][7][8] Percutaneous kyphoplasty (PKP) is a rapid, effective, and minimally invasive technique for treating TLOVFs in elderly patients, and it can speed recovery of function and improve quality of life with fewer complications compared with conservative treatment. [9][10][11][12][13] However, surgeons are heavily dependent on image-guided navigation, especially when the surgeon is inexperienced.…”
Section: Introductionmentioning
confidence: 99%
“…Fractures of the thoracolumbar spine represent 42.4%–75.2% of all spinal fractures, followed by lumbar and cervical spine fractures 1–4 . Thoracolumbar osteoporotic vertebral fractures (TLOVFs) are the most common complication of osteoporosis and can not only affect patients' work and daily life but also lead to other functional disorders, spinal deformities, and sometimes even paralysis 5–8 …”
Section: Introductionmentioning
confidence: 99%